A "Self‐Checking" pH/Viscosity‐Activatable NIR‐II Molecule for Real‐Time Evaluation of Photothermal Therapy Efficacy. (21st February 2022) - Li, Benhao; Liu, Hengke; He, Yaling; Zhao, Mengyao; Ge, Chen; Younis, Muhammad Rizwan; Huang, Peng; Chen, Xiaoyuan; Lin, Jing
Abstract: We present a second near‐infrared (NIR‐II) self‐checking molecule, LET‐1052, for acidic tumor microenvironment (TME) turn‐on photothermal therapy (PTT), followed by viscosity based therapeutic efficacy evaluation by itself in two independent channels, denoted as "self‐checking" strategy. In acidic TME, LET‐1052 was protonated and turned on NIR‐II absorption for PTT under 1064 nm laser irradiation. Subsequently, PTT‐induced cellular death increases intracellular viscosity, which inhibited the intramolecular rotation of LET‐1052, resulting in the enhancement of NIR‐I fluorescence for real‐time evaluation of PTT efficacy. After PTT of tumor‐bearing mice for different periods of NIR‐II laser irradiation, NIR‐I fluorescence in the tumor region showed positive correlation with tumor growth inhibition rate, demonstrating reliable and prompt prediction of PTT efficacy. The strategy may be expanded for instant evaluation of other therapeutic modalities for personalized medicine. Abstract : A second near‐infrared (NIR‐II) self‐checking molecule, LET‐1052, was developed for visualizing intracellular viscosity change and immediately predicting therapeutic efficacy of tumour turn‐on photothermal therapy.